Indonesia - hendika aprilian; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Abstract Sempor Village Nature Tourism Area is an area located in Sempor Village, Kebumen, Central Java. Located on a hill near Sempor Reservoir, the natural potential is to become a very promising tourist spot, not only as a tourist place but as a place of sports and natural education, namely camping for visitors who come and are suitable for all ages ranging from young children to adult. In addition, tourism in the natural tourist area in Sempor Village is by the presence of duck boat tours, reservoir boat tours, and photo taking places. The tourist area, located in Sempor Village, was synthesized in the form of planning and design concepts. This development plan seeks to provide a function of tourism potential that accommodates local and long-distance tourist activities with natural themes with an organic architecture approach. The applied concept of organic architecture seeks to unite natural and environmental conditions with land and buildings